2022
DOI: 10.3390/molecules27020404
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Characterisation of Macroaggregated Human Serum Albumin: Strength and Specificity of Bonds with 99mTc and 68Ga

Abstract: Background: Macroaggregated human serum albumin (MAA) properties are widely used in nuclear medicine, labelled with 99mTc. The aim of this study is to improve the knowledge about the morphology, size, dimension and physical–chemical characteristics of MAA and their bond with 99mTc and 68Ga. Methods: Commercial kits of MAA (Pulmocis®) were used. Characterisation through experiments based on SEM, DLS and Stokes’ Law were carried out. In vitro experiments for Langmuir isotherms and pH studies on radiolabelling we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Some authors have assumed that 99m TcO 4 − reduced by the Sn(II)- albumin aggregates probably formed a (Tc = O) 3+ complex with the aggregates [ 15 ]. More recently, high positive cooperativity was shown between 99m Tc and MAA, although MAA particles did not seem to have binding pockets [ 18 , 19 ]. Moreover, it has been shown that the speed of radiolabelling increased from HAS to albumin nanocolloids (NC) to MAA due to the greater reaction surface [ 18 ].…”
Section: Lung Perfusion Imagingmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have assumed that 99m TcO 4 − reduced by the Sn(II)- albumin aggregates probably formed a (Tc = O) 3+ complex with the aggregates [ 15 ]. More recently, high positive cooperativity was shown between 99m Tc and MAA, although MAA particles did not seem to have binding pockets [ 18 , 19 ]. Moreover, it has been shown that the speed of radiolabelling increased from HAS to albumin nanocolloids (NC) to MAA due to the greater reaction surface [ 18 ].…”
Section: Lung Perfusion Imagingmentioning
confidence: 99%
“…More recently, high positive cooperativity was shown between 99m Tc and MAA, although MAA particles did not seem to have binding pockets [ 18 , 19 ]. Moreover, it has been shown that the speed of radiolabelling increased from HAS to albumin nanocolloids (NC) to MAA due to the greater reaction surface [ 18 ]. This result agreed with the hypothesis, which assumed that in HAS labelling kits, Sn 2+ may be enclosed in the tertiary structure of the protein and that it may take some time for the 99m TcO 4 − added to diffuse the site of Sn 2+ for reduction reaction [ 17 ].…”
Section: Lung Perfusion Imagingmentioning
confidence: 99%
See 3 more Smart Citations